The relationship of situational efficiency parameters of volleyball game phases and their intrateam variability with the set score - Klaricic, I.; Grgantov, Z. (Proceedings of the 11th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2023)
The purpose of this study is to determine the relationship between situational efficiency parameters of five phases of the volleyball game and their intrateam variability with the set score. A sample of 40 volleyball sets played in the European League for Men in 2011 and 2012 were randomly selected. Although, the sample wasn`t recent, the purpose of this methodologically based study was to propose a new performance indicator. The multiple regression analysis determined a high and positive relationship between the situational efficiency of five phases of the volleyball game with the set score. It also determined that the intrateam variability between the phases of the volleyball game had a statistically significant but negative relationship with the set score. The variability of game phases explained 4.1% of the variance of the score. Conclusion was that a larger negative deviation in situational efficiency of one phase of the game cannot be compensated only by the corresponding incre ase in another phase of the game, as the linear regression model suggests.